2020
DOI: 10.1080/07391102.2020.1790425
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bioactive molecule from Withania somnifera (Ashwagandha) as SARS-CoV-2 main protease inhibitor

Abstract: SARS-CoV-2 is the causative agent of COVID-19 and has been declared as pandemic disease by World Health Organization. Lack of targeted therapeutics and vaccines for COVID-2019 have triggered the scientific community to develop new vaccines or drugs against this novel virus. Many synthetic compounds and antimalarial drugs are undergoing clinical trials. The traditional medical practitioners widely use Indian medicinal plant Withania somnifera (Ashwagandha) natural constituents, called wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 70 publications
(46 reference statements)
2
103
0
Order By: Relevance
“…It is also predicted that withanone and withaferin-A can interact with transmembrane protease serine 2 (TMPRSS2), thereby potentially could block the entry of SARS-CoV-2 into host cells [75]. A combination of withanone and caffeic acid phenethyl ester [76] or withanoside-V [77] has also been predicted to inhibit SARS-CoV-2 activity by interacting with its main protease (M pro ). Anti-viral properties of ursolic acid [78] and betulinic acid [79] have been reported, with ursolic acid also inhibiting M pro under in silico conditions [80].…”
Section: Discussionmentioning
confidence: 99%
“…It is also predicted that withanone and withaferin-A can interact with transmembrane protease serine 2 (TMPRSS2), thereby potentially could block the entry of SARS-CoV-2 into host cells [75]. A combination of withanone and caffeic acid phenethyl ester [76] or withanoside-V [77] has also been predicted to inhibit SARS-CoV-2 activity by interacting with its main protease (M pro ). Anti-viral properties of ursolic acid [78] and betulinic acid [79] have been reported, with ursolic acid also inhibiting M pro under in silico conditions [80].…”
Section: Discussionmentioning
confidence: 99%
“…In order to rank different proposed SARS CoV-2 Mpro inhibitors, the binding free energy of these inhibitors was compared with the DG bind of "Mpro-N3 interaction" (Alamri et al, 2020;Ghosh et al, 2020aGhosh et al, , 2020bKumar et al, 2020;Tripathi et al, 2020). Many proposed Mpro inhibitors including phytochemicals (such as withanone, caffeic acid, epigallocatechin gallate, epicatechingallate, gallocatechin-3-gallate etc.…”
Section: Binding Free Energy Estimation Using Mm-gbsa Analysismentioning
confidence: 99%
“…Furthermore, various phytochemicals are also proposed as the SARS CoV-2 main protease inhibitors through screening and structure-based design approach (Gorla et al, 2020;Gurung et al, 2020;Mazzini et al, 2020). In recent times, it has been found that plant-derived polyphenols can serve as potent SARS CoV-2 Mpro inhibitors (Bhardwaj et al, 2020;Ghosh et al, 2020aGhosh et al, , 2020bTripathi et al, 2020). Our group has identified three polyphenols from green tea [epigallocatechin gallate (EGCG), epicatechingallate (ECG) and gallocatechin-3-gallate (GCG)] can inhibit the catalytic activity of SARS CoV-2 Mpro (Ghosh et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Protein preparation was done by using the protein preparation wizard of Schr€ odinger maestro, where hydrogen atoms were added and water molecules were removed. Sidechains and loops were built using the prime module (Madhavi Sastry et al, 2013) and the ligand preparation was done by using the Ligprep module (Tripathi et al, 2020). The OPLS-2005 force field was used for further optimization and minimization of the protein and ligand structures.…”
Section: Protein and Ligand Preparationmentioning
confidence: 99%